Synthesis Of Glycerol Carbonate From Glycerol And Urea Using Limestone As Catalyst Source - Megawati Megawati (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Synthesis of Glycerol carbonate from glycerol and urea using limestone as a catalyst has been conducted. This study aims to make glycerol carbonate from glycerol and urea by utilizing scattered natural limestone widespread in Southeast Sulawesi as a catalyst source. The catalyst was obtained from the calcination of natural limestone to decompose CaCO3 to CaO. This condition added to glycerol and urea to test the catalyst activity. Synthesis of glycerol carbonate was carried out through the carbamoylation reaction of glycerol with urea. The advantage of this method is the reaction carried out with free solvents and running in ambient pressure (1 atm). The stages of catalyst testing in the reaction of glycerol carbonate formation were carried out by reacting glycerol, urea, and calcined limestone  with  1: 1 substrate mole ratio with a catalyst concentration of 5% mass over glycerol. Characterization used was Fourier Transform Infrared Spectroscopy (FTIR) and supported by Gas Chromatography (GC) data. Optimization catalysis reaction was obtained at a temperature of 140oC for 4 hours and  using a catalyst mole ratio to 5% substrate